Penguatan Pelaporan Keuangan Koperasi Wanita Sri Rejeki Berbasis General Ledger - Anisykurlillah, Indah; Latifah, Lyna; Fachrurrozie, Fachrurrozie; Permatasari, Yoan; Fuad, Muhammad Nur (Jurnal Bina Desa, 2025)
The purpose of this community service is to build a women's cooperative accounting system based on General Ledger. This system includes cash receipts (loan installments, principal savings, and mandatory/voluntary savings), cash expenditures (loans, savings withdrawals, and operational payments), and financial reporting (balance sheet, reports on remaining operating results, and changes in equity). The approach used is Participatory Rural Appraisal (PRA) through counseling, mentoring, and training. The target of the activity is the management and members of the Sri Rejeki Women's Cooperative Semarang totaling 10 people. Community service activities include mentoring in preparingsavings and loan formssuch as installments, loans, savings, and voluntary savings using General Ledger. Meanwhile, training includes preparing forms and financial reports for cooperatives based on General Ledger. The results of the community service show that the management can understand and prepare loan forms, voluntary savings withdrawals, and cooperative operational payments based on General Ledger, and are able to prepare balance sheets, reports on remaining operating results, and reports on changes in equity.